Виявлення сучасних та предкових субліній штамів родини Beijing у київській популяції Mycobacterium tuberculosis - Чередник, Ю.О.; Анопрієнко, О.В.; Барбова, А.І.; Журило, О.А. (Фактори експериментальної еволюції організмів, 2015)
Aims Characterization of M. tuberculosis Beijing family in Kyiv’s clinical strains population by content of «modern» and «ancient» sublineages as defined by structure of NTF locus. Methods. Multiplex PCR of NTF locus, ETR-VNTR, and SNP-typing (katG463) of bacterial isolate DNA samples from Kyiv’s patients with pulmonary tuberculosis. Results. 19 clinical isolates of M. tuberculosis strains belonged to the PGG-1 by SNP-typing and to two of the most prevalent ETRVNTR Beijing genotypes (42435, 42434) showed NTF-locus structure characteristic to «modern» type. Conclusions. More samples should be analyzed to determine the proportion of «ancient» Beijing subtypes in Kyiv M. tuberculosis population. Alternative quick and convenient methods for detection of these sublineages could be considered for more effective strategy of M. tuberculosis monitoring in Kyiv. Keywords: Mycobacterium tuberculosis, molecular epidemiology, NTF-locus.